Application of a full body inertial measurement system in alpine skiing: A comparison with an optical video based system - Krüger, A.; Edelmann-Nusser, J. (Journal of Applied Biomechanics, 2010)
This study aims at determining the accuracy of a full body inertial measurement system in a real skiing environment in comparison with an optical video based system. Recent studies have shown the use of inertial measurement systems for the determination of kinematical parameters in alpine skiing. However, a quantitative validation of a full body inertial measurement system for the application in alpine skiing is so far not available. For the purpose of this study, a skier performed a test-run equipped with a full body inertial measurement system in combination with a DGPS. In addition, one turn of the test-run was analyzed by an optical video based system. With respect to the analyzed angles, a maximum mean difference of 4.9° was measured. No differences in the measured angles between the inertial measurement system and the combined usage with a DGPS were found. Concerning the determination of the skier`s trajectory, an additional system (e.g., DGPS) must be used. As opposed to optical methods, the main advantages of the inertial measurement system are the determination of kinematical parameters without the limitation of restricted capture volume, and small time costs for the measurement preparation and data analysis.